Effect of Integrating Banana at Early Stages on Growth of Areca catechu in Multitier Agroforestry System - Panwar, Pankaj; Medda, P.S.; Suresh, C.P.; Chaudhury, P. (Indian Journal of Agroforestry, 2020)
An experiment was conducted to find out effect of integrating banana with arecanut in agroforestry system. Banana and arecanut plants were grown in the year 2003. After first harvest of banana in December, 03 the banana suckers were managed in such a way that they could maintain specific light intensity, varying from 25 800 (x 100) lux, on the areacanut plants growing adjoining to it. The data on growth performance of arecanut was taken for two years and was compared with the plants which were growing in full sunlight. It was found that height, collar girth, number of exposed nodes, leaf length and width, number of leaflets and leaf numbers of arecanut plants growing in 100 x1 00 Lux was highest. It was also found that as the intensity of light decreased further the growth performance of the plants also decreased.